INVENTARISASI DAN IDENTIFIKASI MORFOLOGI TANAMAN GARUT (Maranta arundinaceus L.) DI KABUPATEN JEMBER - Kacung Hariyono; Vega Kartika Sari; Riza Yuli Rusdiana; Indri Fariroh; Widya Kristiyanti Putri; Didik Pudji Restanto; Luluk Noviana (Jurnal Penelitian Pertanian Terapan, 2022)
The aim of this study is to identify the arrowroot morphology characters and its distribution pattern in Jember District, East Java Province. Plant inventory was carried out in 6 sub-districts, i.e. Arjasa, Sumbersari, Silo, Tanggul, Semboro, and Wuluhan from July to October 2021 using survey method. The sampling technique was done by accidental sampling. The results of dendogram analysis based on morphological characters showed that Sumbersari, Wuluhan, and Arjasa were sub-district areas with a lot of arrowroots, if compared to other 3 sub-districts. Three main groups were formed based on the similarity of arrowroot morphological characters, accessions from geographically adjacent sub-district or village had greater morphological similarities. Leaf length has a close relationship with leaf width, leaf sheath length, and leaf petiole diameter. The distance between stem segments has a correlation with stem height. The longest fibrous roots and stem diameter contributed less to arrowroot diversity. The number of internodes positively correlated with tuber circumference, tuber length, and tuber weight. Arrowroot plant accessions grew in groups according to certain morphological characteristics, which was also showed a close relationship between these accessions. Keywords: accession, arrowroot, genetic relationship, morphological characteristic